PREHISTORIC ARCHAEOLOGY IN NORTHERN AUSTRALIA - Harry Allen (BRIN, 1986)
The northern part of North Australia is not far from Java and Timor. There are great numbers of influences in the North Western part of Australia from Indonesian region. The coast alligator river area is 200 kilometres east of Darwin, Northern Territory is now 60 kilometres from the coast to the mountain area. The plain area is flat and the water is salty, being tidal on the coast. Further inland the river is fresh water. To day there are few mangroves in this area, but there is evidence that mangroves were more widespread between 6.000 - 3.000 BP. During the wet season the coastal plain is flooded.